The Photography of Decolonization / The Decolonization of Photography: an image from the Algerian War of Independence - Fysh, William (Revue CMC Review, 2014)
<!–[if gte mso 9]> <![endif]–> In May 1961, an anonymous French photojournalist took a picture for Agence France Presse depicting a group of pro-independence fighters released from an internment camp near Sétif in Algeria. In the image, several of these men look back to the camera holding framed portraits of the French president, Charles De Gaulle. In the following analysis, I explore how this photograph dramatizes a deeply ambiguous historical moment. In May 1961, the Algerian War was in the balance. On the one hand, De Gaulle was beginning negotiations with pro-independence leaders in an attempt to end the war. On the other, the dissident paramilitary wing of the French army – L’Organisation de l’armée secrète - had recently launched operations in Algeria and mainland France aimed at undermining De Gaulle’s overtures for peace and preserving l’Algérie française at any cost. As a result, this photograph dramatizes the visual rhetoric of the official presidential portrait at a moment in which the person of the president and the system of imperial governance he embodied were most under threat. In this photograph, both the meaning of De Gaulle and French imperial power are in suspension. Building on visual culture theorist Nicholas Mirzoeff’s formulations of “visuality” and “countervisuality,” I explore how this photograph recontextualizes the visual rhetoric of the presidential portrait. By returning the presidential gaze back to the camera and the viewer, I argue, this photograph simultaneously reaffirms and destabilizes the semiotics of state power, offering competing visions of an Algerian future. I conclude by exploring how, even as this image renders state power ambiguous, it also records a particular moment of performed solidarity that challenges political sovereignty (either French or Algerian) outright - an instance of what Mirzoeff calls “the right to look.” <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–>